2014
DOI: 10.1021/jf404355b
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Excretion of Perfluorooctane Sulfonate (PFOS) in Beef Cattle (Bos taurus)

Abstract: Perfluorooctane sulfonate (PFOS), a perfluoroalkyl surfactant used in many industrial products, is present in industrial wastes and in wastewater treatment plant biosolids. Biosolids are commonly applied to pastures and crops used for animal feed; consequently, PFOS may accumulate in the edible tissues of grazing animals or in animals exposed to contaminated feeds. There are no data on the absorption, distribution, and excretion of PFOS in beef cattle, so a 28-day study was conducted to determine these paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 36 publications
9
59
1
Order By: Relevance
“…A similar evidence was noted in the experimental trials on broilers (Yeung et al, 2009). Uncertainty arise in the above mentioned studies as well as in the studies by Numata et al (2014) and by Lupton et al (2014) due to low sample size, due to unclear resulting internal exposure levels and a lack of information about the degree of convergence at the steady state level. In the current modeling we considered the carry-over rates computed on the lowest experimental doses reported, because it is assumed as more in line with reported water quality, under the assumption that the PFOS in water can be transferred to the food webs via the disposal of wastewater-derived sludges on arable lands, thus leading to bioaccumulation in farmed and wild animals of alimentary interest ( Figs.…”
Section: Toxicokinetics and Residues In Food Of Animal Originsupporting
confidence: 62%
“…A similar evidence was noted in the experimental trials on broilers (Yeung et al, 2009). Uncertainty arise in the above mentioned studies as well as in the studies by Numata et al (2014) and by Lupton et al (2014) due to low sample size, due to unclear resulting internal exposure levels and a lack of information about the degree of convergence at the steady state level. In the current modeling we considered the carry-over rates computed on the lowest experimental doses reported, because it is assumed as more in line with reported water quality, under the assumption that the PFOS in water can be transferred to the food webs via the disposal of wastewater-derived sludges on arable lands, thus leading to bioaccumulation in farmed and wild animals of alimentary interest ( Figs.…”
Section: Toxicokinetics and Residues In Food Of Animal Originsupporting
confidence: 62%
“…Lupton et al . found that PFOA was mainly eliminated by urine in cattle, while PFOS was minimally eliminated through urine and it could be transported to the bile and then eliminated in feces or reabsorbed by the intestinal tract4748. A previous study also implied that the biliary excretion rate of PFOA was higher than that of PFOS due to the higher reabsorption rate of PFOS through the enterohepatic circulation process in humans30.…”
Section: Discussionmentioning
confidence: 99%
“…The elimination half-lives of PFBA and PFOA differ by one order of magnitude for monkeys and by three orders for man (Table 2) [201,202]. Angus cattle was a fast excreter for PFOA, with a 1 mg/kg bw dose being totally excreted (urine) within nine days [203], but not for PFOS, for which about one third of the dose (8 mg/kg bw ) was still present in the plasma after 28 days, thus becoming a potential exposure source for carnivorous humans [204]. Greatly different kinetics for PFOS and PFHxS versus PFOA and PFBA were confirmed in cows fed with contaminated feed [157].…”
Section: Animal (Including Human) Data Show Widely Different Pharmacomentioning
confidence: 99%